ChurchMorph : how megatrends are reshaping Christian communities - Gibbs, Eddie (Grand Rapids, Mich. : Baker Academic, 2009)
Church observer Eddie Gibbs goes beyond an analysis of the causes to show how many churches and faith communities are actually breaking the downward trend. He expertly maps current converging church movements--emerging and missional churches, mainline renewal groups, megachurches, urban mission, new monasticism, alternative worship, and expanding networks--and offers a positive assessment of the reshaping of today's church. --from publisher description
Introduction -- Megatrends convulsing the western world -- Post-christendom churches -- Interlude : identifying the streams -- Fresh expressions -- The megachurch factor -- Urban engagement -- Resurgent monasticism -- Expanding networks -- The heartbeat of worship -- Conclusion -- Appendix: Distinctive features of morphing churches.
Includes bibliographical references (p. 207-216) and index.
Keywords: Church renewal; Church growth; Communities -- Religious aspects -- Christianity; Postmodernism -- Religious aspects -- Christianity